Expectativas prévias ao implante coclear e avaliação pós implante em adolescentes - Murakami, Gisele Aparecida De Oliveira; Neme, Carmen Maria Bueno [UNESP]; Yamada, Midori Otake; Bevilacqua, Maria Cecília (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2001)
This work aimed to verify tendencies of relation between previous expectations (P.E.), anxieties and fears of patients applying to Cochlear Implant (C.I.) and their later evaluation concerning the gains obtained with the implant. The subjects were 6 patients of both sexes, between 13 and 19 years of age, with C.I. accomplished from 7 to 44 months. The data previous to the surgery were collected from the patients registers and compared with the ones collected through the semi-structured interview conducted during the later rehabilitation stage. The results indicated similarity between two kinds of P.E. and evaluation post C.I.. The aesthetic aspect revealed itself as an important factor among the patients concerns. The pre-surgery guidance made the P.E. more adequate as well as the evaluation of the gains post C.I.. The necessity of psychological attendance pre and post C.I. is indicated in order to minimize the difficulties of adaptation related to the self-image of adolescent patients and the development of proper expectations.

O trabalho objetivou verificar tendências de relação entre expectativas prévias (E.P.), ansiedades e temores de pacientes candidatos a Implante Coclear (I.C.) e suas avaliações posteriores quanto a ganhos obtidos com o implante. Os sujeitos foram 6 pacientes, de ambos os sexos, entre 13 a 19 anos de idade com I.C. realizado de 7 a 44 meses. Dados anteriores à cirurgia foram coletados dos prontuários e comparados aos coletados via entrevista semi-estruturada na fase de reabilitação posterior. Resultados indicaram similaridade entre tipos de E.P. e avaliações subseqüentes ao I.C.. O aspecto estético mostrou-se importante fator de preocupação. A orientação pré-cirúrgica facilitou adequação de E.P. e avaliações de ganhos pós implante. Indica-se a necessidade de acompanhamento psicológico pré e pós I.C. para minimizar dificuldades de adaptação relacionadas à auto-imagem de pacientes adolescentes e adequação de expectativas.
Previous expectations concerning cochlear implant and post implant evaluation in adolescents
Keywords: Expectativas Prévias; Implante Coclear; Adolescente; Auto Imagem; Previous Expectations; Cochlear Implant; Adolescence; self-image